Advancements and techno-economic viability of pole-integrated vertical PV tubes: Evaluating alternatives to conventional flat panels in arid and low-maintenance environments – A review article - Khaled A’amar (21165317) (2025)
The increasing demand for sustainable energy solutions has driven the expansion of pole-installed photovoltaic systems (PIPVS), particularly in remote and arid environments where conventional energy infrastructure is impractical. However, pole-mounted flat PV panels (PMFPVP) suffer from significant performance limitations due to shading, dust accumulation, high maintenance costs, and energy storage inefficiencies. These challenges necessitate frequent cleaning and system oversizing, making them less viable for low-maintenance applications. In response, this review examines the potential of Pole-Integrated Vertical PV Tubes (PIVPVT) as an alternative technology that mitigates these issues while enhancing energy output stability and reducing maintenance requirements. This study employs a comprehensive review methodology, integrating an arithmetic analysis of polygonal VPVT designs with an in-depth techno-economic comparison of VPVT and FPVP systems. The analysis includes a structural evaluation of VPVT materials, operational cost assessments, and a case-based economic feasibility study under different environmental conditions. Key performance indicators such as shading resilience, dust accumulation impact, cleaning costs, and lifecycle economic viability are examined to establish VPVT’s competitiveness against conventional flat PV panels. The results indicate that while VPVT systems have higher initial capital costs, they offer substantial long-term advantages, particularly in non-maintainable or high-dust environments. VPVT technology reduces energy storage requirements by maintaining a more stable power output curve throughout the day, minimizes shading losses due to its cylindrical structure, and significantly lowers cleaning frequency and associated operational costs. The findings highlight VPVT as a sustainable and economically viable alternative to flat PV panels in pole-mounted applications, particularly for urban, arid, and remote locations where conventional systems are constrained by maintenance challenges. This research contributes to the growing body of knowledge on low-maintenance PV technologies and provides a roadmap for future deployments of VPVT systems in sustainable energy infrastructure. Other Information Published in: Solar Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.solener.2025.113517